STRATEGI PENGEMBANGAN TEACHING INDUSTRY PADA PERGURUAN TINGGI NEGERI - Tri Maryugo Hawati; Suyono Suyono; Mesa Ardhi Nugroho (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2019)
The purpose of this study is to formulate strategic priorities in order to elaborate "Teaching Industry" activities at State Universities. In this study, we use descriptive analysis and Analytical Hierarchy Process (AHP) methods. The results of this study show that percentage of budget realization for Fiscal Year 2016 until 2018 is quite high, the precentage mean around 98% per year, however the number of State Universities participating in the Teaching Industry activities is still low, in 2016 as many as 6 Legal Entity State Universities, and in 2017 and 2018 as many as 8 Legal Entity State Universities. This is due to the remained subdued regulations that support the program and funding gap from the Government, State University, and Industry. Further more, in order to developing the Teaching Industry activities there are still many obstacles including, regulations that have not been supported, insufficient funding and the quality of human resources. The strategy in an effort to develop a Teaching Industry activities analyzed by AHP in order of quality and priorities is as follows: 1) compile regulations related to governance, institutions, and the Teaching Industry business model with a weight of 0.27; 2) coordinate intensively through the formed of a special team with a weight of 0.18; 3) improve the quality of lecturers and researchers through scholarship and entrepreneurship training programs with a weight of 0.16; 4) provide incentives / grants for university and industry cooperation with a weight of 0.15; 5) compile monitoring and evaluation instruments for the implementation of the Teaching Industry with a weight of 0.13; 6) improve university facilities and infrastructure with a weight of 0.11. For sensitivity analysis, shows that a scenario changes for Teaching Industry do not have an impact on changes in the priority of the strategy resulted. Keywords: Strategy, Teaching Industry, State University, Analytical Hierarchy Process (AHP). Abstrak Tujuan dari kajian ini adalah untuk merumuskan prioritas strategi dalam upaya mengembangkan kegiatan Teaching Industry pada Perguruan Tinggi Negeri. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif dan Proses Hierarki Analisis (PHA). Hasil penelitian menunjukkan bahwa persentase realisasi anggaran Tahun Anggaran 2016 s.d 2018 cukup tinggi, yaitu rata-rata sekitar 98% tiap tahunnya, namun demikian jumlah Perguruan Tinggi Negeri yang berpartisipasi pada kegiatan Teaching Industry masih rendah, yaitu pada Tahun 2016 sebanyak 6 Perguruan Tinggi Negeri Badan Hukum, Tahun 2017 dan 2018 sebanyak 8 Perguruan Tinggi Negeri Badan Hukum (PTN BH). Hal ini dikarenakan masih lemahnya regulasi yang mendukung program tersebut dan kurang kuatnya pendanaan baik dari sisi Pemerintah, Perguruan Tinggi maupun Industri. Selain itu, dalam mengembangkan kegiatan Teaching Industry juga masih terdapat banyak kendala diantaranya, yaitu: regulasi yang belum mendukung, keterbatasan pendanaan, dan kualitas sumber daya manusia. Strategi dalam upaya mengembangkan kegiatan Teaching Industry yang dianalisis dengan proses hierarki analisis sesuai dengan urutan bobot dan prioritasnya adalah sebagai berikut: 1) menyusun regulasi terkait tata kelola, kelembagaan, dan model bisnis Teaching Industry dengan bobot sebesar 0,27; 2) melakukan koordinasi secara intensif melalui pembentukan tim khusus dengan bobot sebesar 0,18; 3) meningkatkan kualitas dosen dan peneliti melalui program beasiswa dan pelatihan kewirausahaan dengan bobot sebesar 0,16; 4) memberikan insentif/hibah untuk kerjasama Perguruan Tinggi dan industri dengan bobot sebesar 0,15; 5) menyusun instrumen monitoring dan evaluasi pelaksanaan Teaching Industry dengan bobot sebesar 0,13; 6) meningkatkan sarana dan prasarana Perguruan Tinggi dengan bobot sebesar 0,11. Untuk analisis sensitivitas menunjukkan bahwa perubahan scenario tidak berdampak pada perubahan prioritas strategi yang dihasilkan. Kata Kunci: Strategi, Teaching Industry, Perguruan Tinggi Negeri, Proses Hierarki Analisis (PHA).